Unveiling the Power of Transformational Leadership in Faith-Based Schools Through Systematic Literature Review - Rahmatika, Nuniek; Suyatno; Mohammad, Nhelbourne K.; Hartanto, Dody; Abdullah, Abduljabbar (International Journal of Learning Reformation in Elementary Education, 2025)
This study aims to explore the impact of transformational leadership in faith-based schools through a systematic literature review. It investigates how religious values and spiritual principles shape leadership styles and school performance. By analyzing various studies, this research highlights how transformational leadership rooted in religious values can drive increased motivation and engagement among staff and students in pursuit of educational excellence. The findings indicate that leadership approaches integrating spiritual, moral, and social awareness enhance both professional effectiveness and personal well-being among school leaders. Faith-based school leaders utilize religious values as a resource to strengthen transformational leadership practices. Integrating principles such as service, sacrifice, and compassion, derived from religious doctrines, enhances leadership efficacy and fosters a value-centered educational climate. This study makes a significant contribution to improving the quality of education and leadership in faith-based schools.